Framing the future of privacy: citizens’ metaphors for privacy in the coming digital society - Matti Minkkinen; Burkhard Auffermann; Sirkka Heinonen (Springer, 2022)
Privacy is one of the pressing issues of the digital age. New technologies and surveillance practices continuously present new privacy threats. This paper reports an exploratory qualitative study on non-experts’ metaphors for privacy in future society using focus group material from three countries: Finland, Germany and Israel. Using thematic analysis, four metaphorical frames for privacy are constructed: ‘dodo’, ‘hemline’, ‘savings’ and ‘foundations of our home’. The frames are analysed using the causal layered analysis method to uncover their systemic and worldview components. Taken together, the metaphorical frames highlight two key concerns of individuals: their struggle for control over a dominating future, on the one hand, and the problem of trust in collective means of privacy protection, on the other hand. The article concludes that the views of non-experts need to be included in broad societal discussion about a desirable future society and the role of privacy in that society. This discussion needs to seriously consider systemic interconnections that challenge privacy as well as the whole ecosystem of metaphorical frames for privacy.